2000
DOI: 10.1088/0022-3727/33/4/306
|View full text |Cite
|
Sign up to set email alerts
|

Determination of sea-water cut-off frequency by backscattering transfer function measurement

Abstract: The temporal frequency response of water supplemented with scattering particles was deduced from the measurement of the optical backscattering of a short (100 ps) blue-green (532 nm) optical pulse given by a frequency-doubled Nd:YAG laser. Indeed, this backscattering measurement gave the water impulse response from which the transfer function was computed by taking the power spectrum. This backscattering frequency response had a low-pass filter-like response which enabled us to estimate the medium cut-off freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…Mullen et al found that the backscatter had a lowpass filter-like frequency response, with a cutoff frequency proportional to the beam attenuation coefficient [3]. This result was experimentally verified by Pellen et al, which found that the backscatter's frequency response decreases at approximately 20 dB/decade for frequencies above 100 MHz [4]. These results motivate the use of high carrier frequencies to take advantage of the physical characteristics of the underwater optical channel.…”
Section: ି௭mentioning
confidence: 84%
See 1 more Smart Citation
“…Mullen et al found that the backscatter had a lowpass filter-like frequency response, with a cutoff frequency proportional to the beam attenuation coefficient [3]. This result was experimentally verified by Pellen et al, which found that the backscatter's frequency response decreases at approximately 20 dB/decade for frequencies above 100 MHz [4]. These results motivate the use of high carrier frequencies to take advantage of the physical characteristics of the underwater optical channel.…”
Section: ି௭mentioning
confidence: 84%
“…Based on theory and previous experiments, the SIR for a band centered at 1 GHz should be approximately 20 dB greater than that of a band centered at 100 MHz [3][4]. The gain for BSS is not expected to depend on frequency, because the BSS algorithm is transparent to the choice of a specific transmit signal or frequency band.…”
Section: Figurementioning
confidence: 99%
“…(2) and (3) may become more complicated due to the possible presence of a multiple-scattered component. However, simulations run on using a semi-analytical Monte Carlo treatment as described by Poole et al 9 showed us that, under our experimental conditions, this contribution was limited because of both the small numerical aperture of the detection system and the relatively low scattering coefficients (c < 1 m -1 ).…”
Section: B(t)= W(t)* E(t)mentioning
confidence: 99%
“…As the target return is less frequency-dependent, the use of a radiofrequencymodulated laser source along with a narrow band filtering at the detection drastically reduces the backscattering clutter 3,4 , but has no effect on the target return; the modulation frequency of the source must be clearly above the cut-off frequency of the propagating medium. This high-frequency modulated-lidar detection scheme was initially proposed by Mullen et al 5 then developed by Pellen et al 6 within our laboratory through experiments carried out in a water tank 2,6 . The amplitude-modulated laser pulse was obtained through use of an optical delay line system placed after a 100-ps-pulse Nd:YAG laser frequency-doubled at 532 nm.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, if a sufficiently large amount of photons scattered back into the receiver field of view, this can cause the system to erroneously detect an "object" at the center of the scattering distribution rather than detecting the desired object. Scattering has typically been mitigated by applying high modulation frequencies to the laser, as backscatter has been shown to have a lowpass frequency response [1,2], In terms of backscatter reduction, this work will focus on the application of digital signal processing algorithms to improve performance by processing the received signal rather than depending solely on the physics of the underwater channel. Although absorption and scattering are two separate physical phenomena, their effects on water conditions are often combined together into a single parameter, the attenuation coefficient c, which has units of Tn"-'-.…”
Section: Introductionmentioning
confidence: 99%